Development of Two Tossa Jute Mutants for Higher Fiber Yield Through Mutation Breeding (Research in Agriculture Livestock and Fisheries, 2024)
The demand for jute fiber is increasing instead of synthetic fiber nowadays. Developing an early and high fiber-yielding tossa jute line is the main breeding objective of jute growing areas including Bangladesh. To fulfill that objective, the existing cultivar JRO-524 was irradiated with five (700, 800, 900, and 1000 gy) doses of gamma-ray.  A total of 25 M3 plants were first selected from bulked M2 plants. Two years of replicated yield trial experiments were conducted in different locations in Bangladesh. Among them, two mutants BJM-10-1-3 and BJM-10-1-5 were selected for higher fiber and stick yield. The selected mutants BJM-10-1-3 and BJM-10-1-5 showed 4% to 6% higher yield than their parent JRO-524. The mutant line BJM-10-1-5 showed higher fiber percentage (34.04%), fiber fitness (2.65%), and fiber brightness (44.15%). These two mutants have been under participatory varietal trial (PVT) for evaluation to release a tossa jute variety. These lines will play a vital role in reducing the seed import of variety JRO-524 from India.Vol. 10, No. 3, December 2023: 259-268